Sequential feeding with high-fat/low-crude protein diets for two lines of growing-finishing pigs under daily cyclic high ambient temperature conditions - Fraga, Alícia Zem [UNESP]; Campos, Paulo Henrique Reis Furtado; da Silva, Welex Cândido [UNESP]; Caetano, Raphael Perini [UNESP]; Veira, Alini Mari [UNESP]; dos Santos, Luan Sousa [UNESP]; Hauschild, Luciano [UNESP] (Oxford University Press (OUP), 2019)
This study was conducted to evaluate the effects of sequential feeding technique in two genetic lines (GL; Line A [cross having a greater proportion of Pietrain] and Line B [cross having a lower proportion of Pietrain]) of growing-finishing pigs reared under daily cyclic high ambient temperature conditions. Seventy-eight castrated male pigs (22 ± 2.5 kg BW) were housed in a single group and were allocated to one of the three feeding programs: control (CON, 24 h control diet), high-fat/low-crude protein (HF/LP, 24 h high-fat/low-crude protein diet), and sequential feeding (SEQ, control diet from 1800 to 1000 h and HF/LP diet from 1001 to 1759 h). Cyclic high ambient temperature was induced by exposing the pigs to 22ºC ambient temperature from 1800 to 1000 h (time-period 22ºC, TP22) and to 30ºC from 1001 to 1759 h (TP30). The experimental period lasted 84 days and was divided into 3 growth phases, growing 1 (from day 0 to 20), growing 2 (from day 21 to 48) and finishing (from day 49 to 83). Feed intake was recorded in real time using an automatic feeder system. Pigs were weighed at the beginning and end of each experimental phase. Animal body composition was measured through dual-energy X-ray absorptiometry on days 0, 35, and 70. The ambient temperature averaged 22.3 ± 0.4ºC during TP22 and 30.2 ± 0.5ºC during TP30, characterizing the condition of daily ambient temperature variation that which pigs are usually exposed in tropical climate areas. During growing phase 1, the feeding programs had negligible effects on pig performance (P > 0.05), whereas during growing phase 2, ADG was greater in SEQ than in CON pigs (7%; P = 0.04). During the finishing phase, HF/LP pigs had greater ADFI (+ 10%) and ADG (+ 8%) than CON pigs. Lean mass and gain did not differ among feeding programs (P > 0.05). Overall, fat mass and gain were similar between SEQ and HF/LP pigs (P > 0.05), and both were greater than those of CON pigs (P < 0.05). On the basis of pig performance per phase, the supply of high-fat/low-crude protein diets (SEQ and HF/LP feeding) improved the performance of pigs under daily cyclic high ambient temperature. However, the use of these techniques resulted in fatter carcasses and in higher energy cost of gain. Finally, pigs with greater proportion of Pietrain genes had decreased growth performance in our experimental conditions.
Keywords: Genotype; Nutrition; Precision feeding; Tropical conditions